A watershed approach to managing rainfed agriculture in the semiarid region of southern Mali: Integrated research on water and land use - Zemadim, Birhanu; Traoré, K.; Gumma, Murali K.; Badolo, F.; Tabo, Ramadjita; Whitbread, Anthony M. (Springer, 2019)
Soil and water conservation (SWC) practices like that of erosion control and soil fertility measures were commonly practiced in the semiarid region of southern Mali since the 1980s. The SWC practices were mainly meant to increase water availability in the subsurface, reduce farm water runoff and gully formation and improve nutrient content of the soil, thereby increasing crop yield. Despite such efforts to promote at scale SWC practices, the landscape of southern Mali is still affected by high rates of runoff and soil erosion and low crop yield in farmers’ fields. Data are lacking on previous beneficial SWC practices that could be adapted for wider application. In this paper, a watershed approach to managing rainfed agriculture is presented to show potential benefits of SWC practices at field and watershed scales. The approach included (1) community participation in establishing and monitoring new sets of hydro-meteorological monitoring stations and field experiments; (2) studying the dynamics and consumptive water uses of different land uses over time; and (3) evaluating the biophysical and economic advantages of SWC practices implemented in the watershed. Results showed that over a period of 34 years (1980–2014) cropping area and consumptive water uses of crops (sorghum and cotton) increased at the expenses of natural vegetation. However, the yield of these crops remained low, indicating that soil fertility management and soil moisture were insufficient. In such cases, implementation of more SWC practices can help provide the additional soil moisture required.